ANALISIS MARKETABLE SURPLUS DAN FAKTOR-FAKTOR YANG MEMPENGARUHI MARKETED SUPPLY SERTA KETERSEDIAAN BERAS DI KOTA BENGKULU - Nusril, Nusril; Romdhon, M. Mustopa; Listaria, Riza (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2008)
This research aim to estimate the amount marketable surplus of rice in Bengkulu City at one season plant March - June 2007; to identify factors influencing marketed supply of rice and to estimate availability of rice in Bengkulu City. Data collected were primary and secondary data. This research location determined using cluster sampling method with respondent of 89 persons selected using simple random sampli. The data analysis were used involving descriptive and multiple regression analysis estimated using ordinary least square method. The result show that : 1) percent marketable surplus of rice in Bengkulu City is 57,58%, the ret is 42,62%; 2) Factors influencing marketed supply of rice in Bengkulu City are : Rice price, cultivation index, and status of paddy farm.